Die aard en aanbieding van die leksikografiese definisie - Lombard, F.J. (Lexikos, 1991)
The Nature and Presentation of the Lexicographical Definition The lexicographical definition is still the most important entry in a dictionary article. It is important that this significant entry, like other dictionary entries, should rely on the dynamics of real language. To achieve this, it is necessary that the lexicographer must base his definitions on citations from the spoken and written language. This important aspect of lexicography is touched on. I also take a look at different ways that the lexicographer can use to compile definitions. The best known methods probably are genus and differentiae definitions, synonym definitions, circle definitions and descriptive definitions. Various criteria can be applied to test the lexicographical definition. I limit myself to comprehensiveness, clarity, accuracy, consistency, autonomy, objectivity and neutrality, which I believe to be the most important criteria. Keywords: lexicographical definition; real language; genus and differentiae definitions; synonym definitions; circle definitions; descriptive definitions; comprehensiveness; clarity; accuracy; consistency; autonomy; objectivity; neutrality; componential analysis; user-friendliness; polysemy